Oral health care: the knowledge and work of the community health agent - Venancio,Elizandra de Queiroz (2014)
Introduction: With the reorganization of oral health policy in 2004, the community health agent is regarded as a facilitator of oral health practices in her area.Objective: To identify knowledge and practice of community health agents in oral health care.Material and method: This is a qualitative study, based on the theory of social representations, and the data were collected through semi-structured interviews, using the collective subject discourse as the technique of tabulation and analysis of data. The sample consisted of 11 interviews, delimited by saturation. Data collection was conducted during the period April-June 2010, in Dourados, Mato Grosso do Sul.Result: The results indicate that respondents understand what oral health is, realize the impact of oral health on overall health, guide the community regarding oral health carein their work practices, operate and provide care in the basic health unit, but have not been trained to act as instructors.Conclusion: The community health workers have knowledge of common sense oral health, acquired through their own life experiences and observation of the world, but show some uncertainty due to lack of training.This points to the need for investment in ongoing education for these professionals so that they can continuously assist the population in the process of empowerment of knowledge about health.